Benfotiamine improves functional recovery of the infarcted heart via activation of pro-survival G6PD/Akt signaling pathway and modulation of neurohormonal response - Katare, Rajesh (2010)
Benfotiamine (BFT) is a transketolase activator that directs glucose to the pentose phosphate pathway. The present study investigated whether BFT improves the recovery after myocardial infarction (MI) and explored underlying mechanisms of protection. Non-diabetic and streptozotocin-induced type 1 diabetic mice were supplemented with BFT (70 mg/kg/day in drinking water) for 4 weeks and then subjected to MI or sham operation. Cardiac function was monitored by echocardiography. At two weeks post-MI, intra-ventricular pressure was measured by Millar tip-catheter and hearts were collected for biochemical, immunohistochemical and expressional analyses. No treatment effect was observed in sham-operated mice. Post-MI mortality was higher in diabetic mice and hemodynamic studies confirmed the worsening effect of diabetes on functional recovery. Furthermore, diabetic mice demonstrated increased cardiomyocyte apoptosis, reduced reparative angiogenesis, larger scars, enhanced oxidative stress, and blunted activation of the pro-survival VEGF receptor-2/Akt/Pim-1 signaling pathway. BFT improved post-MI survival, functional recovery and neovascularization and reduced cardiomyocyte apoptosis and neurohormonal activation in diabetic as well as in non-diabetic mice. In addition, BFT stimulated the activity of pentose phosphate pathway enzymes, leading to reduction of oxidative stress, phosphorylation/activation of VEGF receptor-2 and Akt and increased Pim-1, pBad and Bcl-2 levels. These effects were contrasted on silencing glucose-6-phosphate dehydrogenase, the key enzyme in pentose phosphate pathway, or inhibiting Akt. BFT benefits post-MI recovery through stimulation of pro-survival mechanisms and containment of neurohormonal response. These results may have implications for the treatment of myocardial ischemia.